Persuasive Communication Strategies in Consensual Families for Building Family Resilience during Covid-19 Pandemic - Andi Setyawan; Titi Widaningsih; Rahtika Diana (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Persuasive communication is part of family communication that parents usually use to persuade family members, especially children, to direct children to have good personalities and characters. Persuasive communication is in line with the type of consensual family, which is a family that has high conversation and conformity. The application of good persuasive communication in consensual families will lead to solid family resilience, namely families that are resistant to external threats. At the beginning of 2020, Indonesia experienced a national disaster with the COVID-19 pandemic. Data from the DKI Jakarta Health Office in February 202 stated that the most significant contributor to COVID-19 was the family cluster. In this condition, family resilience is tested by the threat of COVID-19, resulting in dissonance or imbalance in a family. Therefore, this study wanted to look at persuasive communication strategies in consensual families in forming solid family resilience from the threat of COVID-19 using cognitive dissonance theory. The informant in this study was a consensual family domiciled in the South Petukangan sub-district, South Jakarta. The results showed that the strategies used by the informant's family to maintain family resilience during the COVID-19 pandemic were maintaining a persuasive communication pattern, namely directing, advising, and discussing, parents listening more, spending time together, and playing roles well for all family members. , maintain a caring attitude and mutual understanding, make threats from outside as a form to increase family solidarity, and maintain the parenting pattern that has been carried out so far.